Georgia Architectural and Historic Properties Survey of 204 Walnut Street, Valdosta, Ga., December 1980 - Smith, Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of 204 Walnut Street, Valdosta, Ga., December 1980. One story double pen house of rectangular plan. Gabled tin roof, shed porch with round posts. Shiplap siding. Set on brick piers. Double hung sash windows with 2/2 lights. Date of Construction: App. 1910. Significant as part of a potential N.R. district which would cover a 4 or 5 block area.
Georgia Architectural and Historic Properties Survey of 204 Walnut Street, Valdosta, Ga., December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 3 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 79.1 MB (83,034,887 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Valdosta (Ga.)